La estrategia competitiva como mediadora del efecto de la orientación empresarial en el rendimiento de la empresa: un estudio de pymes registradas seleccionadas en el estado de Ilorin kwara - Oluwayomi Omotayo, Olota (2025)
The ability of SMEs to sustain their performance amid market competition is deeply intertwined with their capacity to adopt and implement innovative business strategies. Hence, this paper aims to investigate competitive strategy as a mediator of the effect of entrepreneurial orientation on firm performance by conducting a study of selected registered SMEs in Ilorin Kwara State. Specifically, it examined the effect of innovativeness, proactiveness, and autonomy on firm performance and competitive strategy as a mediator. A descriptive survey research design was adopted with a population of 1,416 registered SMEs in Kwara State. A sample of 312 SMEs was administered a structured questionnaire. The data collected were analyzed using PLS-SEM. The findings revealed that autonomy has the strongest effect on firm performance (β = 0.401, t = 8.846, p < 0.000), followed by proactiveness (β = 0.219, t = 3.869, p < 0.000), and innovativeness (β = 0.137, t = 2.240, p = 0.026), while competitive strategy has the highest partial mediating effect on the innovativeness-performance relationship (VAF = 52%) followed by the proactiveness-performance relationship (VAF = 24%), but the autonomy-performance relationship (VAF = 8%) has no significant mediating effect. The study concludes that competitive strategy as a mediator is significantly vital for the effect of entrepreneurial orientation on firm performance in selected registered SMEs. Therefore, it is strongly recommended that, to strengthen the firm performance of SMEs, owners should consider competitive strategy in the form of a differentiation strategy and focus strategy, which help to enhance the contribution of entrepreneurial orientation to firm performance as they have a substantial influence on the relationship between entrepreneurial orientation and firm performance.